Characterization of enhanced antibacterial effects of novel silver nanoparticles - Shrivastava S.; Bera T.; Roy A.; Singh G.; Ramachandrarao P.; Dash D. (My University, 2025)
In the present study, we report the preparation of silver nanoparticles in the range of 10-15 nm with increased stability and enhanced anti-bacterial potency. The morphology of the nanoparticles was characterized by transmission electron microscopy. The antibacterial effect of silver nanoparticles used in this study was found to be far more potent than that described in the earlier reports. This effect was dose dependent and was more pronounced against gram-negative bacteria than gram-positive organisms. Although bacterial cell lysis could be one of the reasons for the observed antibacterial property, nanoparticles also modulated the phosphotyrosine profile of putative bacterial peptides, which could thus affect bacterial signal transduction and inhibit the growth of the organisms. © IOP Publishing Ltd.